Involving the community : a guide to participatory development communication - Bessette, Guy, 1952- (Southbound ; International Development Research Centre, 2004)
This guide is intended for people working in research and development. It introduces participatory development communication concepts, discusses the effective two-way communication approaches, and presents a methodology to plan, develop, and evaluate communication strategies to address the following questions: How can researchers and practitioners improve communication with local communities and other stakeholders? ; How can two-way communication enhance community participation in research and development initiatives and improve the capacity of communities to participate in the management of their natural resources? ; How can researchers, community members, and development practitioners improve their ability to effectively reach policymakers and promote change?